Peran Bantuan Hukum dalam Melindungi Korban Ketidakadilan - Abdi Syahputra Ritonga; Muhammad Alfiansyah (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
Access to justice is a constitutional right that is often difficult for vulnerable groups to access, thus triggering legal disparities and systemic injustice. This study aims to analyze the urgency of legal assistance by advocates and Legal Aid Institutions (LBH) as a protection instrument for individuals facing legal arbitrariness. Using normative legal research methods supported by a statute approach, this study evaluates the effectiveness of the implementation of the Legal Aid Law in Indonesia. The results show that legal assistance functions not only as technical representation in court, but also as a balancing power relationship between the state or powerful entities and citizens. Legal assistance plays a vital role in mitigating violations of legal procedures (due process of law) often experienced by victims of injustice. However, structural obstacles such as limited state budgets and low public legal literacy remain major obstacles. This study concludes that strengthening the free legal aid scheme (pro bono publico) integrated with strict judicial oversight is essential to ensure that justice belongs not only to those with financial resources, but also to all citizens without exception.